An Optimization Method to Determine Optimum Carbonization Temperature of Banana Stems Based Activated Carbon for Supercapacitors. (August 2019) - Taer, Erman; Purnama, Agrandi; Apriwandi,; Agustino,; Taslim, Rika; Mustika, Widya Sinta
Abstract: The optimization of carbonization temperature was obtained by experimental design, assisted by using a 3rd-order polynomial equation, for use in supercapacitor application. Activated carbon monoliths are produced based on the carbonization temperatures of 500 °C, 550 °C, 600 °C and 650 °C. The monolithic activated carbon samples were characterized based on their physical properties, including density, degree of crystallinity and surface morphology, and their electrochemical properties, including specific capacitance, energy and power. The optimum conditions, which yielded a minimum electrode density and steak height as well as a maximum combination of energy and power, were found to be at a temperature of approximately 550 °C. In addition, the exact minimum and maximum carbonization temperatures that correlated with density, steak height and a combination of energy and power were found by a simulated mathematical model to be 543 °C, 544 °C, and 553 °C, respectively. The surface morphology was analyzed and was used as supporting data. In conclusion, by experimental and mathematical simulation, the optimum carbonization condition was obtained more accurately.